Hydrogen and fluorine migration in photo-double-ionization of 1,1-difluoroethylene (1,1-C2H2F2) near and above threshold - Gaire, B.; Bocharova, I.; Sturm, F. P.; Gehrken, N.; Rist, J.; Sann, H.; Kunitski, M.; Williams, J.; Schöffler, M. S.; Jahnke, T.; Berry, B.; Zohrabi, M.; et al. (My University, 2014)
We have studied the nondissociative and dissociative photo-double-ionization of 1,1-difluoroethylene using single photons of energies ranging from 40 to 70 eV. Applying a coincident electron-ion three-dimensional momentum imaging technique, kinematically complete measurements have been achieved. We present the branching ratios of the six reaction channels identified in the experiment. Electron-ion energy maps and relative electron emission angles are used to distinguish between direct and indirect photo-double-ionization mechanisms at a few different photon energies. The influence of selection and propensity rules is discussed. Threshold energies of double ionization are extracted from the sum of the kinetic energies of the electrons, which hint to the involvement of different manifolds of states. The dissociative ionization channels with two ionic fragments are explored in detail by measuring the kinetic energy release of the fragment ions, sum of the kinetic energies, as well as the energy sharing of the two emitted electrons. We investigate the migration of hydrogen and fluorine atoms and compare the experimental results to the photo-double-ionization of centrosymmetric linear and planar hydrocarbons (C2H2 and C2H4) whenever possible.